Tindakan Penyalahgunaan Stiker Wajah Tanpa Izin di Whatsapp : Telaah Undang-Undang Hak Cipta dan Undang-Undang ITE - Sarini Abudi; Nirwan Junus (Universitas Kapuas, 2026)
The rapid development of digital communication has raised complex legal issues, including the misuse of personal data. One such practice is the creation of WhatsApp stickers using other people’s photos without consent. This study analyzes this practice from the perspective of the Electronic Information and Transactions (ITE) Law and the Copyright Law, as well as examining the factors contributing to its persistence. This research employs a normative juridical method by analyzing primary and secondary legal materials. The findings indicate that the use of unauthorized photos as WhatsApp stickers constitutes a violation of both the ITE Law and the Copyright Law. Photographs are classified as electronic documents that must be legally protected from misuse. The creation and distribution of such stickers infringe upon ownership rights and moral rights of the individuals depicted. Despite these legal provisions, the practice continues due to low legal and ethical awareness, its perceived function as entertainment, and the ease of using WhatsApp’s features. Strengthening legal awareness and digital ethics is therefore essential to prevent such violations.